Studi Optimasi Pola Tanam Daerah Irigasi Kosinggolan Di Kabupaten Bolaang Mongondow - Rudson, Rony; Soetopo, Widandi; Limantara, Lily Montarcih L (Fakultas Teknik, Universitas Brawijaya, 2014)
Irrigation areas of Kosinggolan which is spread in Dumoga plains has potential broad in 5381 acres and irrigated functional areas 3865 acres at this time. After 28 years in operation Kosinggolan weir discharge decreased that effect on agricultural production. Due to the discharge limitations in Kosinggolan implementing the provision of irrigation water the class system is divided into three planting periods. Linier Optimization and Sensitivity Analysis to the crop pattern has been using Solver facility from Microsoft Excel.Based on the results ofthe conducted optimization analysis obtained extensive results optimum crop rice at dry conditions, condition low, under normal conditions and sufficient conditions: crop rice from 1450 – 3865 acres. While the maximum profit results in dry conditions, under conditions of low, under normal conditions and sufficient conditions: from Rp 11.133.750.357,00 until Rp33,200,350,000,00. For sensitivity analysis results of obtained land area sensitive: in dry conditions between, the low condition, under normal conditionsand the sufficient conditions: from 0–9307 acres.Keywords: irrigation, linier optimization, sensitivity